Bibliometric Review of Climate Change Adaptation Financing - Erfendi Regar; Ilham Akbar Bunyamin; Rani Eka Arini (Westscience Press, 2026)
The objective of the current study is to investigate the intellectual structure, evolution of themes, and research collaboration within the research area of climate change adaptation finance through bibliometric analysis. In this regard, data were gathered from the Scopus database and analyzed through VOSviewer in order to investigate co-authorship network structure, citation network structure, and keywords cocitation patterns. It was found that the conceptual development of the research area takes place in the context of core themes, such as climate change, adaptation, and finance; however, it also evolves beyond these themes into interdisciplinarity of topics, such as risk management, sustainability, governance, and environmental economics. The trend in the analysis of keywords demonstrates the evolution of research themes from the initial focus on economy and policy to the later focus on investment, adaptive management, and adaptation in specific sectors. Finally, the analysis of co-authorship and institutional affiliations demonstrates that the research area of climate change adaptation finance is concentrated within a limited number of clusters with contributions coming primarily from the United States and other institutions; however, the participation of developing countries in this research area is increasing.